2022
DOI: 10.3390/cancers14143343
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health-Related Quality of Life and Completion of First-Line Treatment among Lung Cancer Patients

Abstract: Experts recommend assessing lung cancer patients’ health-related quality of life (HRQOL) in the diagnostic evaluation. We investigated the association between HRQOL and completion of first-line treatment among lung cancer patients in a prospective cohort study. Clinical information on lung cancer patients was obtained from medical records, and information on quality of life and lung cancer-related symptoms was obtained through questionnaires at time of diagnosis. We used directed acyclic graphs to identify pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(59 reference statements)
0
2
1
Order By: Relevance
“…One explanation could be our use of the relatively new thresholds for clinical importance, 18 as previous studies that have dichotomized functioning and symptoms measured with the QLQ-C30 commonly set cutoff values below 66 and above 33, respectively. 41,42 In contrast, the cutoff for dyspnea in the present study was >17. 18 This new cutoff may provide a better indication of the…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…One explanation could be our use of the relatively new thresholds for clinical importance, 18 as previous studies that have dichotomized functioning and symptoms measured with the QLQ-C30 commonly set cutoff values below 66 and above 33, respectively. 41,42 In contrast, the cutoff for dyspnea in the present study was >17. 18 This new cutoff may provide a better indication of the…”
Section: Discussioncontrasting
confidence: 75%
“…It is well‐known that long‐term survivors experience substantial fatigue and pain, 40 but dyspnea has to our knowledge not previously been reported as a severe symptom experienced by cancer survivors. One explanation could be our use of the relatively new thresholds for clinical importance, 18 as previous studies that have dichotomized functioning and symptoms measured with the QLQ‐C30 commonly set cutoff values below 66 and above 33, respectively 41,42 . In contrast, the cutoff for dyspnea in the present study was >17 18 .…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, cognitive QOL alone was not significantly associated with survival. Numerous studies on cognitive QOL in patients with lung cancer have reported less decline compared to other functional QOL [67][68][69]. This is likely because there is little variation in cognitive QOL values and that patients with cognitive decline tend to be excluded from clinical trials [60,68].…”
Section: Discussionmentioning
confidence: 99%